Keanekaragaman dan kelimpahan semut pada perkebunan kakao di Jawa Timur: pengaruh kondisi habitat dan keberadaan tropobion - Yuniasari, Novita; Yuliastanti, Nely; Himawan, Toto; Rizali, Akhmad (Perhimpunan Entomologi Indonesia, 2021)
Habitat conditions around cocoa plantations which include canopy cover and lower vegetation (weeds) as well as the presence of mealybugs trophobiont (Planococcus sp.) can affect the diversity and abundance of ants. The objective of this research was to study the diversity and abundance of ants in cocoa plantations and to study the effect of habitat conditions and the presence of trophobiont (Planococcus sp.) on species richness and ant abundance. The research was carried out in 12 locations spread across five districts in East Java. Ant samples were collected by tuna bait and direct collection. The results obtained 5,475 individuals and 8 species of ants. The most dominant ants and found in all areas were Dolichoderus thoracicus (Smith) and Technomyrmex albipes (Smith). Based on the regression analysis, there is a relationship between canopy cover and vegetation diversity with ant species, but not with abundance, meanwhile the presence of trophobiont shows a positive correlation with ant abundance. The habitat conditions for cocoa cultivation and the presence of trophobiont affect the diversity and abundance of ants in cocoa plantations.